Production of Multilayered Nanostructure from Zingiger Officinale by Spray Pyrolysis Method (Global Journal of Science Frontier Research, 2018)
This present work describes exploring cost-effective a natural renewable Environmentfriendly green precursor for the synthesis of Multi-walled carbon nanotubes (MWCNTs) using methyl ester of Zingiber officinale oil over Fe-Co impregnated alumina support at 850°C under N 2 atmosphere. The characterization of the as-grown carbon materials was analyzed by Scanning electron microscopy (SEM), Highresolution transmission electron microscopy (HRTEM), XRD and Raman spectroscopic analysis. The bimetallic catalyst of Fe and Co supported on alumina gel particles improves the quality and uniformity in diameters of CNTs. The diameters of assynthesized nanotubes are in the range of 22 nm to 24 nm.
Keywords: CNTs; spray pyrolysis; SEM; HRTEM; raman